Proposta de um sistema de gestão da efetividade de cursos de engenharia - Pinto, Felipe Pereira (2023)
This text presents research related to the effectiveness of engineering teaching. It was carried out in the context of the creation of a transformation office for the Graduate Course in Industrial Systems Engineering at the Federal University of Goiás (CGEP-UFG). The objective of the study was to propose an effectiveness management system (EMS) capable of measuring the degree to which an engineering course fulfills its purpose, and thus support the direction of its transformation initiatives. In order to deal with this socio-technical challenge, the method adopted followed the greater logic of action research, where the investigation effort interferes with the investigated object. The peculiar nature of the research object led to careful contextualization of the systemic approach to guide the intervention. There was a conscious effort to situate the object's life cycle as an engineered system, that is, as a system created by human beings, endowed with an objective and subject to interpretation of effectiveness. Thus, the influence of the engineering approach itself in bringing an engineering course into existence was recognized, which, when in operation, creates engineers who, in turn, contribute to engineering other systems for the benefit of society. Following this rationale, some principles of Systems Engineering and Design Science Research (DSR) were adopted in order to pursue this hierarchical ordering of considerations. The method led to the creation of an effectiveness model based on the principles advocated by the CDIO Initiative (Conceiving-Designing-Implementing-Operating), which was configured based on survey fundamentals and instrumented as part of the SGE. In this way, a means of converting subjective perceptions of 12 intangible attributes into a normalized quantitative framework was established. A scale of 0 to 100 was adopted for each effectiveness attribute that makes up the model, where 0 represents empty and 100 represents full. The implementation of the SGE at CGEP-UFG provided an illustration of the functioning of the measurement instrument, through which the value of 47 was measured for the current state of effectiveness of the course, calculated from 37 individual evaluations collected. These results should be expanded in future works in order to provide statistical interpretations with a greater degree of confidence. Its use in the real case described here evidences the materialization of a sophisticated feedback loop: the current effectiveness informs transformation decisions that affect the effectiveness in the future – ideally establishing a powerful virtuous cycle of evolution. Given its generic structure, the SGE can be integrated into any engineering course.